Payroll tax, employment and labor market concentration - Erick Baumgartner; Raphael Bottura Corbi; Renata Narita (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2025)
How much employment can be generated by decreasing payroll taxes? We examine this question by exploring the staggered rollout of a large payroll tax reform in Brazil. Using administrative matched employer-employee data, we find an increase of 5 percent on employment due to both firm growth and firm entry, no impact on wages and a significant increase in profits. Moreover, employment effects are driven by less concentrated labor markets, consistent with predictions from an oligopsony model.
Keywords: H2; J3; J6; J42; 330; Payroll Tax; Employment; Wages; Profits; Oligopsony